Development of Computational-based Visualization Method in Physical Chemistry Practical Course - Gani Purwiandono (International Journal of Science and Applied Science: Conference Series, 2017)
Study on the development of computational-based visualization method in Physical Chemistry practical course has been carried out. The study was carried out by combining the conventional method and the visualization using the software. This combination class then was compared to the conventional class of the practical course. The cognitive evaluation showed that the distribution of students’ understanding for the supporting theory of the practical course was not significantly different. The students had relatively the same level of understanding regarding the supporting theory. The evaluation of learning outcomes and the distribution of final grade showed that the class which combined the conventional and visualization method gave a positive result in the learning process